A conceptual framework on the Quality of Life (QOL) factors that can improve mental health conditions among underprivileged children - Zamzuri, Farah Akmal Mohd; Herman, Siti Sarah (MAJ - Malaysia Architectural Journal, 2023)
There is a pressing need to address mental health problems among the underprivileged children in Malaysia as reported by the RoyalMalaysia Police (PDRM) whereby, children between 15-18 years old, made up 51 per cent of the total 1,708 suicide cases recorded. Previous studies found that mental health problems are prevalent among young people in Malaysia yet access to specialist mental health care is extremely limited. In relation to that, there seems to be a lack of rehabilitation centres, for current mental health services, and the design space conducive to the healing process and wellbeing of these underprivileged children. Hence, the objective of the concept paper is to review on the current literature review on children’s quality of life, children’s mental health and children’s healing environment inorder to formulate a conceptual framework on the rehabilitation centre for underprivileged children to enhance their wellbeing and quality of life. In this research, a case study will be used as the research inquiry to provide a greater understanding of the contextual environment of the subject and allow asking questions and following up on issues. This research will explore architectural guidelines on the rehabilitationcentre for underprivileged children to enhance their wellbeing and quality of life. Furthermore, this research will contribute to the local authority councils to provide shelter as well as design guidelines on the rehabilitation centre for unprivileged children. Future research can do survey questionnaires towards bigger sampling.